Ensuring prehospital care in thermal injuries: experience from an explosion in a textile factory - Hadac, V (Acta chirurgiae plasticae, 2002)
The objective of this work was to inform about the performance of the rescue service, in collaboration with other members of an integrated rescue system, in responding to an event in which several subjects suffered burn injuries. Proper organization of the work by a doctor of the rescue group at the site of the explosion, the work of the rescue service dispatchers, and the coordination of the activities of the different rescue teams are the prerequisite for the successful avoidance of the sequelae of mass disasters.
Keywords: záchranná práce; urgentní zdravotnické služby; Accidents, Occupational; Explosions; pracovní nehody; Rescue Work; lidé; Textiles; exploze; popálení; Burns; textilie; Emergency Medical Services; Humans